ANALISIS ORGANOLEPTIK PADA HASIL OLAHAN SOSIS IKAN AIR LAUT DAN AIR TAWAR - Ridawati Marpaung; Asmaida . (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
This research aims to do analysis organoleptik of fish sausage processed sea water and freshwater fish in order to diversify fisheries results processing. This experimentwas performed experimentally using a complete Randomized Design (RAL), with 5 (five) factors of the treatment are: S1 = sausage from fish catfish; S2 = sausage fromcatfish; S3 = sausage from the shrimp; S4 = sausage from tunaS5 = sausage from sardinesFrom the analysis results and test DNMRT exhibit organoleptik flavor, aroma, texture, color, and Favorites on fish sausage processed sea water and fresh water differ markedly from each other. Panelists valuations against the nature of organoleptik flavor, aroma, texture, color and joy of fish sausage processed catfish, catfish and shrimp are preferred compared fish sausage that comes from tuna and sardinesKeywords: processing, fish sausage, organoleptik, diversification